The Relationship Between Renewable Energy Consumption, Net Energy Import, Greenhouse Gas Emission and Human Cap - T. Kiss, Judit; Kocsis, Imre (International Journal of Engineering and Management Sciences, 2018)
The measures to improve energy efficiency and increase of renewable energy production and consumption should be encouraged in the interest of sustainable development. Many factors can influence the use of renewable energy such as the level of economic development of an economy, nationals’ and the main economic actors’ environmental awareness, energy import dependency, ratio of the urban population, and government subsidization intensity among the others. The main purpose of this study is to examine the relationship between the share of renewable energy in the total energy consumption and net energy import as a percentage of energy use less production, greenhouse gas emission per capita and human capital using by OECD countries data from 1990 to 2014. The results indicate that there is a negative relationship between net energy import and renewable energy consumption, and also negative relationship can be shown between the amount of greenhouse gas emission per capita and renewable energy consumption. However, we identified a positive relationship between human capital and renewable energy consumption for energy importer countries above a certain level of human capital.